The Effect of Promotion, Price and Brand Image on the Decision to Choose a Computer Course Institution at Fiara Computer LKP in Selat Besar Village - Arti, Seni; Siregar, Zulkifli Musannip Efendi; Lubis, Junita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to eximine and analyze the effect of promotion, price, and brand image on students decisions to choose a computer course in LKP Fiara Computer. Therefore, Selat Besar Village, Bilah Hilir district, Labuhanbatu Regency. Data Collection was carried out by means of a questionnaire. This study took a sample of 60 respondents from students in 2020 at LKP FIARA Selat Besar, Labuhanbatu. The hypothesis was tested using path analysis using SPSS Version 24 and Amos Version 23. The result of this study indicate that promotion and price have a significant effect on brand image. In this study indicate that promotion and price have a significant effect on brand image. In adition in this study, promotion, price and brand image have a significant influence on the decision to choose a computer course institution at LKP FIARA computer in Selat Besar village, Bilah Hilir District, Labuhanbatu Regency. From the data studied, the promotion, price and brand image can increase promotion in marketing and set prices according ti the image given.